Coupling parallel adaptive mesh refinement with a nonoverlapping domain decomposition solver. (August 2017) - Kůs, Pavel; Šístek, Jakub
Highlights: Massively parallel FEM solver with adaptive mesh refinement. Dynamic load balancing with p4est library. Handling hanging nodes at the interface of subdomains. Parallel solution of the arising algebraic systems by multilevel BDDC. Parallel adaptive FEM computations on 2048 cores with over 10 9 degrees of freedom. Abstract: We study the effect of adaptive mesh refinement on a parallel domain decomposition solver of a linear system of algebraic equations. These concepts need to be combined within a parallel adaptive finite element software. A prototype implementation is presented for this purpose. It uses adaptive mesh refinement with one level of hanging nodes. Two and three-level versions of the Balancing Domain Decomposition based on Constraints (BDDC) method are used to solve the arising system of algebraic equations. The basic concepts are recalled and components necessary for the combination are studied in detail. Of particular interest is the effect of disconnected subdomains, a typical output of the employed mesh partitioning based on space-filling curves, on the convergence and solution time of the BDDC method. It is demonstrated using a large set of experiments that while both refined meshes and disconnected subdomains have a negative effect on the convergence of BDDC, the number of iterations remains acceptable. In addition, scalability of the three-level BDDC solver remains good on up to a few thousands of processor cores. The largest presented problem using adaptive mesh refinement has over 10 9 unknowns and is solved on 2048 cores.